Keadilan, Diskriminasi Dan Sistem Perpajakan Terhadap Penggelapan Pajak - Sasmita, Djenni; Kimsen, Kimsen (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This study aims to determine the effect of justice on tax evasion, to determine the effect of discrimination on tax evasion, and the effect of the taxation system on tax evasion. The results of this study are expected to be useful for the tax office and used as input and consideration in understanding the effect of justice, discrimination and taxation system on taxpayers' perceptions of the ethics of tax evasion. The research method used is qualitative research where the research aims to determine the effect of the independent variable on the dependent variable. The analytical method used is descriptive analysis, instrument test, classical assumption test, hypothesis test and multiple linear equation test. The instrument used is a questionnaire. Based on research and discussion on justice, discrimination, and the tax system against tax evasion. Taxpayers' perceptions of justice, discrimination, and the taxation system together have an effect on tax evasion. This is evidenced by the results of the significance value of the F test of 0.000 which is smaller than 0.05. This means that the better or not the perception of taxpayers regarding justice, discrimination, and the tax system, it will affect the practice of tax evasion in the Tangerang area.